Effect of Video Game on School Achievement in School Age Children in Erbil/City - Nazar Ramadhan Othman; Rozhan Tofiq Khedir; Gulala Kareem Azeez; Kaify Jamil Qadir (Hawler Medical University, 2021)
Background and objectives: Playing video games is associated with poor academic achievement, Student who got their game systems directly spent less time on homework and, four months later, they got lower reading and writing scores, their teachers were more likely to report academic difficulties. The aim of study is to identify the effect of play video game on school achievement. Methods: A cross sectional descriptive study was carried out at five primary school in Erbil city 50 students was taken as a case group compared with 200 students as control group started from 15 September to 15 November 2020. A Questionnaire format was used as a tool for data collection and consists, demographic information of the students, parents and some Items about students game, Official permission has been obtained from College of Nursing / Hawler Medical University, Ministry of Education and primary schools. Data was analyzed through using frequency, percentage and chi-square by using SPSS, 22. Results: The study reveal that 58% of participants were age group between 12-14 years old, 74% of them were boys among playing group, 18% of father were graduated from college, 60% of played children were from middle socioeconomic status, 16% of game players have missed school, 66% of played students were missed homework, about 10% of the students have a good school achievement among who played video games and more than half (58%) among non-play students. There is highly significant association between parent educational levels with their children school achievement. Conclusions: Playing video game was negatively associated with poor school achievement. The study recommended the parent to limit the time of playing less than one hour daily, also limit the number and type of game especially fighting game and replaced with educational game.